PENGARUH MEDIA DAN KOORDINASI MATA TANGAN TERHADAP KETERAMPILAN FOREHAND PADA CABANG TENNIS (experimental studies on thundercat cilegonâ€™s tennis club) - Maulidin, Maulidin; Esser, Balkis Ratu Nurul Laela (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
The objective of this research is to investigate the impact of training medias (using batting tee and hanging ball) and hand-eye coordination of forehand in Tenis. This research is conducted at thundercat cilegonâ€s tennis club. Using 2x2 factorial design. The analysis of variance between groups is at level of significance ï¡ = 0,05.This research also aimed to find out the link between training medias and hand-eye coordination toward forehand skill on tennis. Hand eyes coordination consists of hight and low levels. This research was carried out in thundercat cilegonâ€™s tennis club.The sample consists of 40 athletes who are devided into four group, each group consists of 10 athletes. The data analysis techniques use in this research were two-way analysis of variance (ANOVA) and further continued by Tukey test at ï¡=0,05 level of significance. The results of this research show that (1) in general, forehand skill for group of athletes who trained with the use of batting tee media is better than the group of athlete who were trained with the use of hanging ball media, (2) for hight hand-eye coordination which uses batting tee training media is batter than the which uses hanging ball training media, (3) for low hand-eye coordination uses hanging ball is better than the which uses batting tee training media at ï¡=0,05 level of significance, (4) there is a link between training media and hand-eye coordination toward forehand skill on tennis.